Mechatronic design and development of a non-holonomic omnidirectional mobile robot for automation of primary production. Issue 1 (31st December 2016) - Sharifi, Mostafa; Young, Matthew Samuel; Chen, XiaoQi; Clucas, Don; Pretty, Christopher
Abstract: This paper presents the mechatronic system design and development of a four-wheel drive/steer (4WD4S) mobile robot as a non-holonomic omnidirectional robot, MARIO—Mobile Autonomous Robot for Intelligent Operations. An innovative integrated application of CAD/CAM/CAE and RP has been employed for rapid development of the robot chassis and other mechanical parts by using different software tools. Most of the parts were designed by 3D CAD software which allows further CAE analysis including structural and motion analysis. To reduce the manufacturing time and cost, CAM and RP have been used to manufacture the main parts. These master parts are manufactured by workshop machining and 3D printing. Robot Operating System (ROS) alongside Gazebo simulator have been utilized for modelling, simulation, software development and visualization which enabled to develop the optimum embedded system to control the robot. With this integrated approach, a prototype of MARIO has been developed with a reasonably low manufacturing cost and time.